EXPLORING THE EFFICACY OF ONLINE PROCTORING IN ONLINE EXAMINATIONS: A COMPREHENSIVE REVIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
With the rapid growth of online education, ensuring academic integrity in online examinations has become a significant concern. Online proctoring has emerged as a solution to monitor students remotely during exams, aiming to deter cheating and maintain assessment credibility. This scientific article thoroughly reviews the literature to investigate the effectiveness, challenges, and implications of using online proctoring in online examination settings. A systematic review was conducted by searching electronic databases, including popular scientific databases such as Web of Science, Ebsco, Scopus, and Google Scholar, for relevant articles published between 2018 and 2023. Keywords such as "online proctoring ", "remote invigilation ", "academic integrity "and "online examination "were used to identify pertinent studies. Various research designs, including experimental studies, case analyses, and qualitative assessments, were considered to capture diverse perspectives. The review synthesized findings from existing literature to elucidate the multifaceted aspects of online proctoring in online examinations. Studies highlighted the potential of online proctoring to mitigate cheating behaviors through real-time monitoring, identity verification, and surveillance mechanisms. Proponents of online proctoring argue that it offers a scalable solution to uphold academic standards in online learning environments. Furthermore, some research indicated that students perceive online proctoring as a fair method to ensure equal treatment and transparency during assessments. However, challenges such as privacy concerns, technological issues, and the potential for bias in proctoring algorithms were identified as significant drawbacks. Additionally, the implementation of online proctoring may exacerbate disparities in access to resources and exacerbate test anxiety among students. In conclusion, integrating online proctoring in online examinations presents opportunities and challenges for academic institutions. While online proctoring offers a means to enhance exam security and maintain academic integrity in remote learning environments, its implementation requires careful consideration of ethical, technical, and pedagogical implications. Adopting online proctoring should be balanced with the need to uphold academic standards while ensuring equitable access and promoting student well-being in online education.